Geskiedenis van die Suid-Afrikaanse Weermag in beeld (1912-1987) / Pictorial History of the South African Defence Force (1912-1987) - Erasmus, J.Y. (Scientia Militaria - South African Journal of Military Studies, 2012)
Geskiedenis van die Suid-Afrikaanse Weermag in beeld (1912-1987) / Pictorial History of the South African Defence Force (1912-1987)